Analisis Pengaruh Digital Influencer dan Social Presence Terhadap Purchase Intention yang Dimediasi oleh Customer Trust pada Live Streaming Commerce - Ratnawati, Ratnawati; Hanoky, Alip (Universitas Hamzanwadi, 2023)
The aim of this research is to examine the influence of digital influencers and social presence on consumer buying interest in live streaming commerce in Indonesia through the mediating role of customer trust. The method in this research is a quantitative method, data is collected through distributing online questionnaires with Google Form. The population in this research are consumers who have made online purchases via live streaming commerce. The sampling technique used purposive sampling and obtained 258 respondents. Data analysis used the partial least squares structural equation model (PLS-SEM) with the test tool, namely SmartPls3.0. The research results show that there is an influence of digital presence on customer trust, there is an influence of social presence on customer trust and purchase intention. Apart from that, there is a mediating role of customer trust in the relationship between social presence and purchase intention.